2015
DOI: 10.1038/aps.2014.138
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the therapeutic mechanisms of Xiao-Ke-An in treatment of type 2 diabetes in mice by a Fangjiomics approach

Abstract: Aim: Xiao-Ke-An (XKA) is a traditional Chinese medicine (TCM) formula for the treatment of type 2 diabetes (T2D), and the effective ingredients and their targets as well as the mechanisms of XKA remain to be elucidated. In this study we investigated the therapeutic mechanisms of XKA in the treatment of T2D in mice using a Fangjiomics approach. Methods: KKAy mice feeding on a high-fat diet were used as models of T2D, and were orally treated with XKA (0.75 or 1.5 g·kg -1 ·d -1 ) for 32 d. Microarray mRNA express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 52 publications
(51 reference statements)
0
21
0
Order By: Relevance
“…Besides, catalpol induces antioxidant effects by upregulating the activity of SOD. Catalpol can also downregulate inflammation by suppressing the expressions of various cytokines . Scrophuloside B, another iridoid glycoside obtained from S. ningpoensis , is reported to be a more effective anti‐inflammatory constituent as compared to catalpol.…”
Section: Chinese Herbs As Potential Antidiabetic Retinopathy Therapymentioning
confidence: 99%
“…Besides, catalpol induces antioxidant effects by upregulating the activity of SOD. Catalpol can also downregulate inflammation by suppressing the expressions of various cytokines . Scrophuloside B, another iridoid glycoside obtained from S. ningpoensis , is reported to be a more effective anti‐inflammatory constituent as compared to catalpol.…”
Section: Chinese Herbs As Potential Antidiabetic Retinopathy Therapymentioning
confidence: 99%
“…Zhang, et al [29] presented a-self-developed TCM network pharmacology platform to decipher the network regulation mechanism of qing-luo-yin and to identify active ingredients as well as to guide further experiments. Yang, et al [30] used 1743 Differentially Expressed Genes (DEGs), identified after treating a T2DM mice model with Xiao-Ke-An (XKA), to establish a T2D-specific compound-target-pathway network. Based on the network, they deciphered XKA therapeutic mechanisms mainly by improving carbohydrate and lipid metabolism.…”
Section: Network Pharmacology Is Similar To Multicomponent Multi-targmentioning
confidence: 99%
“…However, the complicated chemical composition also brings great difficulties to the pharmacological investigations of TCM prescriptions. Network pharmacology, which was first proposed by Hopkins2, offers an ideal paradigm to deal with multi-target combination drugs and has recently been successfully adopted to investigate the formulae in TCM34567. The core of the scheme is the construction and analysis of the pharmacological network, which is normally composed of the nodes of active ingredients, the nodes of candidate protein targets, the nodes of intermediate proteins transferring protein-protein interactions (PPI) and the connections (i.e., edges) between them.…”
mentioning
confidence: 99%
“…For example, in the work of Yang et al . on Xiao-Ke-An, 40 chemicals were found from relevant databases while only 20 compounds were identified experimentally5. Moreover, the compounds identified in vitro may not be able to enter the plasma, and thus could not really explain the mechanisms of these TCM formulae.…”
mentioning
confidence: 99%